Interpersonal Communication On Social Stigma Towards Billiard Players Among Students In The Special Region Of Yogyakarta - Erwin Yoga Pratama; Muhammad Najih Farihanto (International Journal Labs, 2025)
This study examines the forms of social stigma faced by pool players in the Special Region of Yogyakarta, as well as the interpersonal communication strategies they use to overcome it. Despite being recognized as an official sport, billiards is often viewed negatively by society and academics due to its association with nightlife and deviant behavior. As a result, pool players often face negative labels, stereotypes, and social and academic discrimination. This study uses a qualitative phenomenological approach with data collection techniques including in-depth interviews, participant observations, and documentation. The study participants were selected based on the criteria of active participation in the sport of billiards and experience in dealing with stigma. The results of the study showed that pool students experienced psychological stress, such as shyness, low self-esteem, and social isolation. However, they are not passive; They use a variety of interpersonal communication strategies as a form of social rejection, including reinforcing self-concept, adjusting interpersonal perceptions, developing positive interpersonal attractions, and maintaining supportive interpersonal relationships. This research supports Goffman's theory of social stigma and Jalaluddin Rakhmat's concept of interpersonal communication. This research makes a significant contribution to our understanding of how communication can be used to maintain personal identity and improve social acceptance in the context of cultural marginalization.